Book review: Krishna, A. 2018. The Broken Ladder: The Paradox and Potential of India's One-Billion. (July 2019) - Rahman, Andaleeb
Krishna, A. 2018. The Broken Ladder: The Paradox and Potential of India's One-Billion . Cambridge University Press. 417 pp. $ 26.90 (Hardcover). ISBN: 978-1108415927